(untitled) (Journal of Artificial Intelligence & Research, 2023)
Microservice architectures (MSA) have become very beneficial for development paradigms to provide time to market for every business. Microservices have evolved as an architectural design pattern. They resolve several old-fashioned development issues like availability, horizontal and vertical scaling, scalability, and ease the maintenance of online services. On the contrary, there are several security breaches have been identified. These breaches have eventually enforced software industry and businesses to reanalysis and redesign the security architecture, remove all security threats, and sustain the confidentiality of microservice-based systems. Micro service containers or PODS one of the most used standards for software application development. a well containerized application includes its libraries, and configuration bundled into one package and ready to be deployed anywhere on cloud platform. By containerizing the application and its dependencies, differences in OS distributions and underlying infrastructures are abstracted away. Therefore, applications developed using containers can be easily deployed in different computing environments. This is particularly important when an application is expected to be deployed in multiple, hybrid cloud environments. However, some characteristics of containers make them hard to manage. For example, containers typically have a short lifespan and are dynamically deployed and scaled. To manage containers, Kubernetes, the de facto standard container orchestration tool, was developed to ease the complexity of running containers. It was originally created by Google but is now an open-source project with worldwide contributors. There are several essential features in Kubernetes for cloud-native applications: We studied and researched several pieces of literature over the web and found a few of them addressing security breaches, and a pragmatic strategy to implement security mechanisms. The aim of this study is to provide a mindful strategy on the detection of all the possible threats on microservices and mitigated or prevented by a potential research gap in securing MSA Method. In this paper, we conducted a systematic real time practical approach to identify the secured and unsecured protocols for microservices deployed in cloud environment. Therefore, we extracted threats and details of proposed solutions reported in selected studies. Obtained results are used to redesign the cloud security. The systematic results we have taken from 150 microservices and found 80% of them unsecured and unprotected. Additionally, we developed solutions which will automatically identify the security issues and automatically replace the ports with secured ones and apply the security tokens Conclusion. More research is needed for identifying the security issues in cloud and replace the unsecured firewalls with the secured one. We recommend that more research on DDOS attacks, Semantic security techniques and research on SSL layers and securing them through DevOps and CI/CD deployment